2018
DOI: 10.1002/btpr.2639
|View full text |Cite
|
Sign up to set email alerts
|

Butanol production from sweet sorghum bagasse with high solids content: Part I—comparison of liquid hot water pretreatment with dilute sulfuric acid

Abstract: In these studies, we pretreated sweet sorghum bagasse (SSB) using liquid hot water (LHW) or dilute H SO (2 g L ) at 190°C for zero min (as soon as temperature reached 190°C, cooling was started) to reduce generation of sugar degradation fermentation inhibiting products such as furfural and hydroxymethyl furfural (HMF). The solids loading were 250-300 g L . This was followed by enzymatic hydrolysis. After hydrolysis, 89.0 g L sugars, 7.60 g L acetic acid, 0.33 g L furfural, and 0.07 g L HMF were released. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The culture could not use all the glucose because it reached butanol/ABE tolerance level. In this fermentation, a productivity of 0.42 gL −1 h −1 and an ABE yield of 0.36 were achieved …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The culture could not use all the glucose because it reached butanol/ABE tolerance level. In this fermentation, a productivity of 0.42 gL −1 h −1 and an ABE yield of 0.36 were achieved …”
Section: Resultsmentioning
confidence: 86%
“…The possible reasons for poor fermentation were either lack of nutrients or lack of sugars in the medium. Control fermentation experiment with glucose and same amount of nutrients suggested that there was no lack of nutrients thus leaving behind the only option of sugar limitation, which further strengthened (see below paragraph) that the culture was not able to hydrolyze the Yellow Top presscake without pretreatment.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies, we investigated the use of SSB, food waste, and YTP to produce bio-butanol [12,29,31]. However, it is important to consider additional factors such as the costs of enzymes, plant size, and consumption of steam and cooling water, all of which affect the cost of producing butanol from the SSB, FW, and YTP.…”
Section: Introductionmentioning
confidence: 99%